Multimedia Interaktif Berbasis Articulate Storyline untuk Melatih Kecerdasan Visual pada Materi ikatan Kimia - Safira Firdaus Yahya; Achmad Lutfi (PendIPA Journal of Science Education, 2023)
The aim of this research was to obtain interactive multimedia based on articulate storylines that have met the valid, practical, and effective categories in training visual intelligence on chemical bonding material. This research uses a type of Research and Development (R&D) research which refers to the 4D development model by Thiagarajan. However, this research is limited only to the development stage. The instruments used were validation sheets, student response questionnaires, and pretest-posttest sheets. Based on the results of the research, it showed that the validity data of multimedia received score of ≥ 3 with a valid category, the practicality data of multimedia obtained from the results of students' responses obtained a percentage of 96.458% with a very practical category, and the effectiveness data of multimedia obtained from the pretest-posttest results analyzed with the Paired Sample T-Test test it got a Significance (2-tailed) value of 0.000 and the pretest-posttest results analyzed with the classical completeness test got a percentage of 90% for the visual intelligence test and 85% for the cognitive test with the effective category. The existence of a relationship between visual intelligence and students' cognitive is shown by the results of the Rank Spearman correlation test with a correlation coefficient value of 0.545 which indicates a strong relationship between visual intelligence and cognitive ability, so it can be concluded that interactive multimedia based on articulate storyline has fulfilled the valid, very practical, and effective category as learning multimedia to train students' visual intelligence which will affect students' cognitive abilities.